Meat quality traits of heavy pigs for the production of traditional Tuscan salami - Mani D.; Balestri G.; Pistoia A.; Casarosa L.; Poli P.; Ferruzzi G. (7th International Symposium on the Mediterranean Pig, 2012)
The objective of the study was to evaluate the effect of the replacement of corn meal (CoM) by chestnut meal (ChM) in two diets of heavy pigs on the quality of meat and traditional Italian Salami obtained. Sixteen Large White pigs were divided in two groups and reared indoors in Garfagnana Valley (Tuscany, Italy). All animals were slaughtered after 464 days of trial at about 228 kg live weight. The quality of the Longissimus lumborum muscle, subcutaneous backfat and salami sausages was evaluated by chemical analysis and fatty acids profile. Data obtained show that ChM group increased the incorporation of unsaturated and monounsaturated fatty acids in muscle and backfat (P<0.05), moreover the diet with ChM significantly reduce (P<0.05) saturated fatty acids in backfat. Particularly ChM diet produced an increase (P<0.05) in the content of C18:1n−9 and significantly (P<0.05) reduce the content of C16:0, C18:0 and C20:0 in backfat. Inclusion of chestnut in the diet seems to have no significant effect on the fatty acid profile of salami. It is concluded that feeding a diet with ChM instead of CoM altered the fatty acid composition of Longissimus lumborum muscle and backfat without simultaneously affecting characteristics of salami sausages quality.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)